Location-Aware Computing Comes of Age - Hazas, Mike; Scott, James; Krumm, John (IEEE Computer, 2004)
At the core of invisible computing is context awareness, the concept of sensing and reacting to dynamic environments and activities. Location is a crucial component of context, and much research in the past decade has focused on location-sensing technologies, location-aware application support, and location-based applications. With numerous factors driving deployment of sensing technologies, location-aware computing may soon become a part of everyday life.